Youth Matters: Philly (YMP): Development, usability, usefulness, & accessibility of a mobile web-based app for homeless and unstably housed youth. (January 2020) - Greeson, Johanna K.P.; Treglia, Daniel; Morones, Seth; Hopkins, Marcia; Mikell, Dominique
Highlights: YMP is a web-based app for searching, identifying, and locating social services. Participants rated overall quality as 3.7 out of 5 on the Mobile App Rating Scale. Engagement, Functionality, Aesthetics, and Information scores ranged from 3.6 to 3.9. YMP is a promising way to increase engagement with social services. Abstract: Background: Young people experiencing homelessness accounted for about 7% of the total homeless population in the United States in 2018. These young people are among the most marginalized youth populations and face numerous hardships. Accessing and connecting with provider organizations is challenging for these young people for myriad reasons related to their marginalization and vulnerability. As a result, homeless and unstably housed youth exhibit low rates of health and social service utilization, despite high rates of need. Objectives: (1) To document the development of a mobile web-based app called Youth Matters: Philly (YMP) for young people experiencing homelessness or unstable housing that is designed to help them search, identify, locate, and utilize Philadelphia-based social and health services; and, (2) To explore youth's perceptions of the usability, usefulness, and accessibility of YMP. Methods: We used the Mobile App Rating Scale (MARS) to assess young people's perceptions of YMP's usability, usefulness, and accessibility. Ten young people who either were currently experiencing homelessness/unstable housing or recently had experienced such hardship participated in the study. During a two-week window, participants logged onto YMP at least three times and searched for resources. They then completed the MARS. Participants were between the ages of 18 and 25 years old (M = 21.5 years; SD = 2.3 years), mostly female (67%), and mostly black/African American (67%). Thirty percent identified as Hispanic/Latinx. All had spent time in foster care and aged out, with an average length of 8.1 years in care ( SD = 4.0 years). We used Qualtrics to collect all data and descriptive statistics to analyze all data in SPSS. Results: The mean scores on the subscales of the MARS (Engagement, Functionality, Aesthetics, and Information) ranged from 3.60 (Aesthetics) to 3.98 (Functionality; Information) out of 5. The mean score for overall Quality was 3.47 (out of 5). We also asked a set of questions specific to YMP to assess perceived impact of the app on the respondents' awareness, knowledge, attitudes, help seeking, and behavior change related to experiencing homelessness and unstable housing. For all questions, at minimum, all participants "somewhat agreed." Conclusions: YMP is a promising way to increase engagement and overcome barriers to accessing services for youth experiencing homelessness or unstable housing. Findings offer insights into ways to improve future versions of YMP. YMP also offers a model for other localities committed to improving access to services for young people experiencing homelessness or unstable housing. Future research directions for YMP and similar technology are discussed.